2011
DOI: 10.1371/journal.pone.0023606
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of NDM-1, a New Antibiotic Resistance Determinant

Abstract: The New Delhi Metallo-β-lactamase (NDM-1) was first reported in 2009 in a Swedish patient. A recent study reported that Klebsiella pneumonia NDM-1 positive strain or Escherichia coli NDM-1 positive strain was highly resistant to all antibiotics tested except tigecycline and colistin. These can no longer be relied on to treat infections and therefore, NDM-1 now becomes potentially a major global health threat.In this study, we performed modeling studies to obtain its 3D structure and NDM-1/antibiotics complex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
47
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 21 publications
11
47
0
Order By: Relevance
“…This study showed that the importance of N 233 depends on the antibiotics tested for NDM-1, consistent with earlier findings for IMP-1 (28). The dramatic loss of activity by K 224 A to most of the substrates tested in this study indicated the critical role of this residue in substrate catalysis, agreeing with the previous study showing that this mutation disrupts the hydrolytic activity of NDM-1 to meropenem (31). NDM-1 appeared to recognize its substrates through the coordination of the ␤-lactam carbonyl, Zn1, and N 233 , as well as the coordination of the carboxylate oxygen atom of the substrate by K 224 .…”
Section: Resultssupporting
confidence: 92%
“…This study showed that the importance of N 233 depends on the antibiotics tested for NDM-1, consistent with earlier findings for IMP-1 (28). The dramatic loss of activity by K 224 A to most of the substrates tested in this study indicated the critical role of this residue in substrate catalysis, agreeing with the previous study showing that this mutation disrupts the hydrolytic activity of NDM-1 to meropenem (31). NDM-1 appeared to recognize its substrates through the coordination of the ␤-lactam carbonyl, Zn1, and N 233 , as well as the coordination of the carboxylate oxygen atom of the substrate by K 224 .…”
Section: Resultssupporting
confidence: 92%
“…5B). The lower affinity of FEZ-1 for meropenem was also simulated in an in silico model by Liang et al (45), which showed no such interactions, except for with the lactam motif. Although the main chain conformation surrounding the C4 carboxylate group differs little between subclass B3 MBLs, the slight difference in the position and orientation of side chains may influence the recognition of ␤-lactams.…”
Section: Resultsmentioning
confidence: 99%
“…10 New Delhi metallo-β-lactmase-1 (NDM-1), a B1 subclass enzyme first discovered in 2008, 11 has become a global threat because it confers resistance to almost all β-lactam antibiotics and due to its rapid spread of the plasmid-encoded NDM-1 gene. 12,13 The inhibitors of serine-β-lactamases (classes A, C, and D), such as tazobactam and sulbactam, have been used in combination with penicillins to treat infections with resistant bacteria. Novel effective MβL inhibitors for such combination therapies are urgently needed.…”
mentioning
confidence: 99%